Ablation of cardiac myosin binding protein-C disrupts the super-relaxed state of myosin in murine cardiomyocytes. (May 2016) - McNamara, James W.; Li, Amy; Smith, Nicola J.; Lal, Sean; Graham, Robert M.; Kooiker, Kristina Bezold; van Dijk, Sabine J.; Remedios, Cristobal G. dos; Harris, Samantha P.; Cooke, Roger
Abstract: Cardiac myosin binding protein-C (cMyBP-C) is a structural and regulatory component of cardiac thick filaments. It is observed in electron micrographs as seven to nine transverse stripes in the central portion of each half of the A band. Its C-terminus binds tightly to the myosin rod and contributes to thick filament structure, while the N-terminus can bind both myosin S2 and actin, influencing their structure and function. Mutations in the MYBPC3 gene (encoding cMyBP-C) are commonly associated with hypertrophic cardiomyopathy (HCM). In cardiac cells there exists a population of myosin heads in the super-relaxed (SRX) state, which are bound to the thick filament core with a highly inhibited ATPase activity. This report examines the role cMyBP-C plays in regulating the population of the SRX state of cardiac myosin by using an assay that measures single ATP turnover of myosin. We report a significant decrease in the proportion of myosin heads in the SRX state in homozygous cMyBP-C knockout mice, however heterozygous cMyBP-C knockout mice do not significantly differ from the wild type. A smaller, non-significant decrease is observed when thoracic aortic constriction is used to induce cardiac hypertrophy in mutation negative mice. These results support the proposal that cMyBP-C stabilises the thick filament and that the loss of cMyBP-C results in an untethering of myosin heads. This results in an increased myosin ATP turnover, further consolidating the relationship between thick filament structure and the myosin ATPase. Highlights: The inhibited super-relaxed state of myosin was measured in permeabilised mouse left ventricles. Severe hypertrophy induced by cMyBP-C ablation was accompanied by a loss of SRX regulation. An intermediate, non-significant decrease in the SRX was noted in trans-aortic constricted mice.